Biological and Chemical control of Fusarium solani caused by disease Root Rot Zea mays - H. jaefar, Olaa (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted to investigate the effect of T. atroviride., Chaetomium spp, bread yeast Saccharomyces cerevisiae, and salicylic acid on F.solani, isolated from the roots of yellow maize plants. Atrophiride T. atroviride and Chaetomium SpP achieved high efficiency in inhibiting F.solani growth on the PDA medium. Yeast was also added to the PDA medium at the concentration 1 g. L-1 inhibition of 68.55%. The factors used in the study all achieved a high degree of reduction in the percentage of the total root injury. Salicylic acid was added with a concentration of 100 mg. kg-1 soil in the first place with a root percentage of 8.33% Yeast then the coefficient Acid Alsalcelik concentration of 50 mg.kg-1 soil and then treated biological fungi Chaetomium spp and T.atroviride The yeast treatment was characterized by the presence of fungus L. F.solani and the lengths were (9.25 and 8 Cm) followed by Salsalic acid treatments and then the two biological fungi Chaetomium spp and T. atroviride compared to the length of plants with the presence of fungus F.solani alone in which the lengths were (4 and 3 cm).